HYDROGEOLOGICAL SYSTEM MODELING OF NONISOTHERMAL GROUNDWATER FLOW IN PIT ABC PT XYZ - SATRIO ADIGUNA (NIM : 12113092), KEVIN
Pit ABC in PT XYZ concession has groundwater flows problems that goes into the pit with high quantities and water temperature reaches 80Ã‚Â°C. This study aims to define the aquifers paramater, create a groundwater flow model in non-isothermal condition which temperature differences are taken using field observations. And then to estimate the groundwater discharge that goes into the Pit ABC at the end of mine life from the contribution of lateral groundwater flow and groundwater flow caused by free convection that enters into the ABC Pit. Data that collected in research area are pumping test data, water sampling for determination of physical and chemical characteristics of water, and groundwater level measurement. Consequently, data from the pumping test at ABC Pit were processed to obtain the aquifer parameteres of the area. Hot water located in the study area is either chlorite or Na-Cl water, characterizing that the water is classified as an connate water or geothermal fluid located in the outflow zone. Secondary and primary data then are processed using Visual Modflow 2010.1 software. The modeling results show that groundwater flow in Pit ABC have nonisothermal conditions caused by convection heat transfer due to below-surface thermal activity and calculations from the zone budget to estimate the flow of groundwater flow into the mine which is 393 liters / second. The contribution of lateral groundwater flow and free convection flow present in the mine has a ratio of 88% lateral flow and 12% free convection flow.